Establishment of a Subgenomic Replicon for Bovine Viral Diarrhea Virus in Huh-7 Cells and Modulation of Interferon-Regulated Factor 3-Mediated Antiviral Response - Horscroft, Nigel (American Society for Microbiology, 2005)
We describe the development of a selectable, bi-cistronic subgenomic replicon for bovine viral diarrhea virus (BVDV) in Huh-7 cells, similar to that established for hepatitis C virus (HCV). The selection marker and reporter (Luc-Ubi-Neo) in the BVDV replicon was fused with the amino-terminal protease N(pro), and expression of the nonstructural proteins (NS3 to NS5B) was driven by an encephalomyocarditis virus internal ribosome entry site. This BVDV replicon allows us to compare RNA replication of these two related viruses in a similar cellular background and to identify antiviral molecules specific for HCV RNA replication. The BVDV replicon showed similar sensitivity as the HCV replicon to interferons (alpha, beta, and gamma) and 2′-β-C-methyl ribonucleoside inhibitors. Known nonnucleoside inhibitor molecules specific for either HCV or BVDV can be easily distinguished by using the parallel replicon systems. The HCV replicon has been shown to block, via the NS3/4A serine protease, Sendai virus-induced activation of interferon regulatory factor 3 (IRF-3), a key antiviral signaling molecule. Similar suppression of IRF-3-mediated responses was also observed with the Huh-7-BVDV replicon but was independent of NS3/4A protease activity. Instead, the amino-terminal cysteine protease N(pro) of BVDV appears to be, at least partly, responsible for suppressing IRF-3 activation induced by Sendai virus infection. This result suggests that different viruses, including those closely related, may have developed unique mechanisms for evading host antiviral responses. The parallel BVDV and HCV replicon systems provide robust counterscreens to distinguish viral specificity of small-molecule inhibitors of viral replication and to study the interactions of the viral replication machinery with the host cell innate immune system.